Plate waste in hospital canteens: a nutritional and environmental analysis in north-eastern Italy - Fiori, Federica; Menis, Diana; Cautero, Peter; Zago, Daniela; Driutti, Marco; Lesa, Lucia; Conte, Alessandro; Scarpis, Enrico; Brunelli, Laura; Parpinel, Maria (Frontiers in Nutrition, 2025)
IntroductionSince the later a food is wasted the greater is its environmental impact, plate waste assessment is crucial to achieve a responsible consumption and production. The aim of this study was to quantify and characterize plate waste generated by users in three hospital worksite canteens in Italy.MethodsUser’s trays were photographed before and after lunch consumption on 5 days. Recipes and portion sizes were provided by canteen staff. A modified Comstock scale was used to quantify plate waste. Carbon footprint, water footprint, energy and nutrient content were estimated.ResultsIn total, 1,227 meals were analysed. The most represented categories were females (56%) and age group 35–54 years old (49%). Plate waste ranged from 2.1% (canteen-3) to 5.9% (canteen-1). Mean plate waste was 32.0 g/tray and 38.5 kcal/tray. However, only 32% of trays contained leftovers. In this subgroup, median plate waste was 78.8 g/tray and 96.0 kcal/tray. Females wasted more than males (6.1% vs. 3.5%). The most wasted categories relative to their served amount were bread, side dishes and salad. Second courses contributed the most to the carbon and water footprint in the total sample, but in two out of three canteens the main contributor were side dishes. These were also the main contributors to the total waste in grams.ConclusionThe goal should not be only to choose a meal with low environmental impact and high nutritional quality, but also to waste less of it. Therefore, this study represents a starting point to shape tailored strategies to reduce plate waste.